ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KAPABILITAS ANGGOTA DPRD TERHADAP PENGAWASAN KEUANGAN (APBD) DAERAH DI KABUPATEN MANOKWARI - Mandacan, Mega Wati; Sabijono, Harijanto; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This study aims to determine the factors that affect the capability of members of parliament to the supervision of local finances (APBD). The variables used in this study are the dependent variable that is the supervision of regional finances (APBD) while the independent variables are personal background, political background, knowledge of DPRD members about the budget. The respondent is a member of the local parliament in the office of the local people's council of manokwari district. This study used multiple linear regression analysis with 30 respondents. The result shows that: (1) Personal Background has a positive influence on Regional Financial Supervision (APBD), (2) Political Background has negative effect on to Local Government Supervision (APBD), (3) Knowledge of DPRD Member on Budget has positive effect toward Local Government SupervisionKeywords : Personal Background, Political Background, Knowledge of DPRD Members About Budget, Regional Financial Supervision